ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIK PADA MATERI BANGUN DATAR DENGAN PENDEKATAN KONTEKSTUAL - akhmad khotib (IKIP Siliwangi, 2019)
The purpose of this study is to see the level of mathematical comprehension ability in a junior high school with contextual approach. the subject of a study was students from class VII, with the number of students 21 people in the quantitative descriptive method. Research instruments are 5 essay questions with indicators of mathematical comprehension ability in Flat Wake material accompanied by interviews with students. The results of the study prove the ability of mathematical understanding in mathematics lessons using a contextual approach to the good category.